Assessment of concentrations of anions in bottled natural mineral waters from the Turkish market in accordance with national and international standards - Gümüş, G.; Destanoğlu, O.; Şimşek, M. G.; Bakır, T. K.; Turhan, Ş (Informa UK Limited, 2021)
In this study, the concentrations of anions (fluoride, nitrite, nitrate, sulphite, sulphate, oxalate, and phosphate) in bottlednatural plain and fruit-flavoured mineral waters of twenty-one commerc...
Keywords: ion chromatography; chemical quality; Bottled mineral water; anions; 6. Clean water